Ketahanan beberapa genotipe kopi terhadap nematoda penggali akar Radopholus similis, Cobb=The Resistance of Some Coffee Genotypes to BurrozvinzNema-tode, Radopholus simflis,Cobb. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
ABSTRACT As the most dangerous of parasitic nematode, Radopholus similis has been causing severe yield losses in a wide range of coffee plantation. Identification of the resistance on coffee germ plasm was the fisrt step to get coffee gene source and root stock for breeding programme. Based on some variable resistance, i.e. biomass seedling weight, number of population nematode, reproductive, root necrotic and decreasing of root weight, the screening test of resistance to Radopholus similis. Cobb had been done on 53 genotypes of genus Coffea. This experiment had been conducted at screenhouse Kaliwining Research Station, designed with complete randomized in three replications. Each treatment had tested in 13 pots and 3 pots treated without inoculation as compared. Using Principal components analysis, canonical discriminant and f astclus analysis, those variables would become new variable, principal components to be classified their resistance in five levels, i.e. resistant, moderate resistant, moderate susceptible, susceptible, and highly susceptible. The results showed that BP 542 A with the smalest symptom index intencity of self pollinated coffee (332.3) was described as the resistant types beside of robusta coffee clone BP 308(633.0)as cross pollinated types,while Excelsa Tjil 490/51 and Excelsa Tjil 490/54 were the resistant types for Liberoid coffee species. The other species that uneconomic value group was described as resistant were Mokka, Stenophylla, Sessiflora, Semperflorence, Congensis and Kapakata. Moreover, those were identified could be improved as new recommended planting material or as rootstock if there was not so high in their yielding ability character.